(i) \(x = \frac{11}{15}\) (ii) \(x = \frac{-13}{17}\)

We need to verify –(-x) = x

Here –x is additive inverse of x.

(i) \(x = \frac{11}{15}\)

Additive inverse of \(x \frac{11}{15}\) is \(\frac{-11}{15}\) = –x

and \(\frac{11}{15} + \frac{{ – 11}}{15} = 0 = \frac{{ – 11}}{15} + \frac{11}{15} \)

we need to find –(-x) that is additive inverse of –x.

Additive inverse of \(-x \frac{-11}{15}\) is \(\frac{11}{15}\) =x

(ii) \(x = \frac{-13}{17}\)

Additive inverse of \(x \frac{-13}{17}\) is \(\frac{13}{17}\) = –x

and \(\frac{-13}{17} + \frac{13}{17} = 0 = \frac{13}{17} + \frac{-13}{17}\)

we need to find –(-x) that is additive inverse of –x.

Additive inverse of \(-x \frac{13}{17}\) is \(\frac{-13}{17}\) = x